Ablatogenomics: can genotype guide catheter ablation for cardiac arrhythmias?. (November 2016) - Roberts, Jason D; Marcus, Gregory M
Previously confined to the management of rare inherited arrhythmia syndromes, a role for genetics within cardiac electrophysiology has begun to emerge for more common arrhythmias, including atrial fibrillation (AF). Catheter ablation for AF is an invasive procedure effective for restoring normal rhythm, however, fails in up to 40% of those undergoing their first procedure and carries a risk for serious adverse events. Recent studies have suggested that a common genetic variant within chromosome 4q25 may be a powerful predictor of procedural success, highlighting the potential of an 'ablatogenomic' strategy. Although still in its infancy, an ablatogenomic approach for AF may facilitate delivery of ablation to those most likely to benefit, while sparing those prone to fail from its risks.